2021
DOI: 10.3389/fimmu.2021.670992
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potentially Therapeutic Immunogenic Peptides From Paracoccidioides lutzii Species

Abstract: Paracoccidioidomycosis (PCM) is an endemic mycosis in Latin America caused by the thermodimorphic fungi of the genus Paracoccidioides spp. Paracoccidioides lutzii (PL) is one of the 5 species that constitute the Paracoccidioides genus. PL expresses low amounts of glycoprotein (Gp) 43 (PLGp43) and PLGp43 displays few epitopes in common with the P. brasiliensis (PB) immunodominant antigen PBGp43, which is commonly used for serological diagnosis of PCM. This difference in structure between the glycoproteins marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
3
0
1
Order By: Relevance
“…There is a consensus that the therapeutic vaccine instead of the prophylactic one would be the best way to control PCM. Several works have demonstrated that a therapeutic vaccine to boost the cellular immune response seems relevant not only to reduce the time of treatment but also to prevent relapses and improve the prognosis of anergic cases [30][31][32]. P10 has previously been well characterized as an epitope for CD4 + T cells [16], and many studies have shown the ability of this peptide to generate a protective immune response against P. brasiliensis in different preparations (Freund's complete adjuvant, Salmonella enterica flagellin FliC) [16,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a consensus that the therapeutic vaccine instead of the prophylactic one would be the best way to control PCM. Several works have demonstrated that a therapeutic vaccine to boost the cellular immune response seems relevant not only to reduce the time of treatment but also to prevent relapses and improve the prognosis of anergic cases [30][31][32]. P10 has previously been well characterized as an epitope for CD4 + T cells [16], and many studies have shown the ability of this peptide to generate a protective immune response against P. brasiliensis in different preparations (Freund's complete adjuvant, Salmonella enterica flagellin FliC) [16,20].…”
Section: Discussionmentioning
confidence: 99%
“…P10 is a major immunoprotective antigen that is being harnessed in vaccine development, and so far, it is the only candidate for vaccination in PCM. The administration of P10 either before or after the establishment of PCM produces a therapeutically protective effect in both immunosuppressed and immunocompetent mice [32]. P10 requires concomitant administration of adjuvant for efficacy, although diverse adjuvants produce a therapeutic effect with the peptide [31], including delivery as a P10-nanoparticle [30].…”
Section: Discussionmentioning
confidence: 99%
“…Na fase inicial da imunidade inata são recrutadas células de defesa informando às células hospedeiras que há uma infecção presente e que a imunidade adquirida deve ser ativada. A imunidade humoral, representada por anticorpos específicos, também é discutida (Silva, et al, 2021;Burger, 2021).…”
Section: Discussionunclassified
“…In addition, the peptide 10 (P10) from the PBGp43 has been explored as a therapeutic, since it can induce protective immune responses in in vitro and in vivo models due its ability to increase proliferation of cells T CD4 + Th1 and the expression of high levels of INF-γ and IL-2. 40 …”
mentioning
confidence: 99%